Treatment for peripheral nerve injury: a protocol for a systematic review and Bayesian network meta-analysis - Shuai Wang; Lili Zhang; Feng Hong; Yuzheng Du; Wenlong Gu; Yongke Yang; Shuting Xu; Huiyan Shi; Xiang-gang Meng (BMJ Open)
Introduction Available therapies for peripheral nerve injury (PNI) include surgical and non-surgical treatments. Surgical treatment includes neurorrhaphy, grafting (allografts and autografts) and tissue-engineered grafting (artificial nerve guide conduits), while non-surgical treatment methods include electrical stimulation, magnetic stimulation, laser phototherapy and administration of nerve growth factors. However, the treatments currently available to best manage the different PNI manifestations remain undetermined. This systematic review and network meta-analysis (NMA) aims to address this and determine the best treatment or combination of treatments for PNI.Methods and analysis A comprehensive search of MEDLINE (via PubMed), Embase, Cochrane Library, Web of Science, Chinese Biomedical Database, China National Knowledge Infrastructure, VIP Database, Wanfang Database, WHO International Clinical Trials Registry Platform, ClinicalTrials.gov and the Chinese Clinical Trial Register will be completed using the following keywords: peripheral nerve injury, therapies and related entry terms. Studies will be included based on specific eligibility criteria, and the reference lists of the included studies will be manually searched. Relevant data will be extracted from the included studies using a specially designed data extraction sheet. The risk of bias in the included studies will be assessed, and the overall strength of the evidence will be summarised. A random-effects model was used for all pairwise meta-analyses (95% CI). Bayesian NMA is used to explore the relative benefits of various treatments. The review will be reported using the Preferred Reporting Items for Systematic Reviews incorporating NMA statement.Ethics and dissemination As the protocol for this systematic review and Bayesian NMA is based on studies with published results and does not involve patient interventions, no ethical review is required. The results will be published in a peer-reviewed journal.PROSPERO registration number CRD42023475135.